Health-related quality of life of stroke patients before and after intervention: Systematic review - Abel Demerew Hailu; Solomon Ahmed Mohammed; Yohannes Shumet Yimer (Journal of Biology and Medicine - Peertechz Publications, 2020)
Stroke, the leading causes of mortality, disability, and has effects on health-related quality of life. The objective of this review is to review the health-related quality of life of patients with stroke. Relevant kinds of literature were searched from Science Direct, Google Scholar, Hinari, Scopus, Web of Science, PubMed, Cochrane Library, and PROSPERO database using inclusion and exclusion criteria. From 864 searched studies, 20 full-text articles were reviewed. Eighty-five percent (n=17) of articles assessed health-related quality of life after the interventions, whereas three (15%) of studies assessed health-related quality of life before the interventions. In 50% (n=10) of studies, physical disability and six (30%) of studies depression occurred as complications of a stroke. Forty percent (n=8), 25% (n=5), 20% (n=4), 20% (n=4), and 10% (n=2) of studies medication therapy, physical exercise, psychological intervention, assistive devices, and surgical procedure were utilized as intervention. The occurrences of stroke complications are determinant for poor health-related quality of life and any of the intervention has a strong and positive impact on health-related quality of life. Any of the interventions and assessments provide important information in deciding and implementing appropriate intervention programs.